PILE FOUNDATIONS USED IN SEISMIC REGIONS - M.M. Bakhromov (Western European Studies, 2025)
The seismic resistance problem of pile foundations; the influence of the design seismicity of the construction site; the horizontal component of seismic actions; the reduction of seismic force due to denser soils; vibrations of the “structure–foundation” system; clay soils and sandy soils; determination of bearing capacity for various soil conditions and for insufficiently studied pile types; and methods for determining the bearing capacity of pile foundations under seismic loading conditions
Keywords: Pile foundations; site seismicity; seismic actions; soil